Perbedaan Beban Kerja dan Kelelahan Kerja Antara Sikap Kerja Berdiri dan Duduk pada Karyawan Bagian Produksi di PT Iskandar Indah Printing Textile Surakarta - Faizah, Isna, Tarwaka, PGDip., Sc., M.Erg, Sri Darnoto, SKM., MPH (2016)
The design of workstations would inevitably influence to the work position which was done by the worker to finish the job. The position of work was devided into two sitting down and standing up position. Working with standing up and sitting down could affect the workload and fatigue. This study aims at knowing the differences of workload and fatique of working between standing and sitting working position on the employees of production departement at PT Iskandar Indah Printing Textile of Surakarta. This research used an observational study with cross sectional approach. The population in this research was the production employees at PT Iskandar Indah Printing Textile Surakarta which includes pakan operators and cucuk operators. The selection of the samples was using the whole populations as many as 60 workers divided into 35 pakan operators and 25 cucuk operators. The bivariate analysis was using the Mann Whitney. The results of statistical tests is for the differences on the workload and fatigue of employment between standing and sitting working position, both of them obtained p value = 0,00. The result can be concluded that there were differences workload and fatigue significantly (p=0,00) between standing up and sitting down working position on employees of production departement at PT Iskandar Indah Printing Textile of Surakarta.